2019
DOI: 10.1016/j.ijbiomac.2019.07.178
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1 binding protein-2 (CBP2) of Plasmodium falciparum binds nucleic acids

Abstract: Several exported Plasmodium falciparum(Pf) proteins contribute to malaria biology through their involvement in cytoadherence, immune evasion and host cell remodelling. Many of these exported proteins and other host molecules are present in iRBC (infected red blood cell) generated extracellular vesicles (EVs), which are responsible for host cell modification and parasite development. CX3CL1 binding proteins (CBPs) present on the surface of iRBC have been reported to contribute to cytoadhesion by binding with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…The internalization of pRBC-EVs by other pRBCs (Mantel et al, 2013;Regev-Rudzki et al, 2013) and their role in intercellular communication affecting malaria pathogenesis have been described in the literature (Mantel et al, 2013;Regev-Rudzki et al, 2013;Saxena et al, 2019;Sisquella et al, 2017). However, to date, of our knowledge, there is no description of the role of EVs in physiological communication between RBCs.…”
Section: Cellular Uptake Of Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…The internalization of pRBC-EVs by other pRBCs (Mantel et al, 2013;Regev-Rudzki et al, 2013) and their role in intercellular communication affecting malaria pathogenesis have been described in the literature (Mantel et al, 2013;Regev-Rudzki et al, 2013;Saxena et al, 2019;Sisquella et al, 2017). However, to date, of our knowledge, there is no description of the role of EVs in physiological communication between RBCs.…”
Section: Cellular Uptake Of Evsmentioning
confidence: 99%
“…These molecular cargos have potential roles in intercellular communication (Regev-Rudzki et al, 2013), modulation of immune response (Saxena et al, 2019;Sisquella et al, 2017), and parasite survival and malaria pathogenesis (Mantel and Marti, 2014;Mantel et al, 2013;Marcilla et al, 2014;Ofir-Birin et al, 2017;Regev-Rudzki et al, 2013). It was also shown that EVs derived from pRBCs can be internalized and transmit genetic material to other pRBCs (Mantel et al, 2013;Regev-Rudzki et al, 2013), monocytes (Sisquella et al, 2017) and endothelial cells (Saxena et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Both, CBP2 as receptor and ATP as ligand were prepared using CHIMERA in PDBQT format. Based on predictions from ATPint & ATPbind and information based on our report of ATP binding to recombinant cCBP2 [19], a grid box was selected to perform the docking. Others parameters for ligand and receptor were set to default [31].…”
Section: Molecular Docking and Interaction Analysismentioning
confidence: 99%
“…It is believed that PfSBP1 resides in Maurer's clefts and works with other proteins like MAHRP1, Pf322, REX1, and REX2 to transport PfEMP1 [18]. The cytoplasmic domain of CBP2 (cCBP2) is also known to directly bind PfSBP1, nucleic acids (DNA/RNA) and ATP [19]. Furthermore, both PfSBP1 and CBP2 have been found to be present in extracellular vesicles (EVs) produced by parasitized RBCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation